Comparative analysis of upwelling influence between the western and northern coast of the Iberian Peninsula - Alvarez, I. (2019)
Upwelling conditions have been simultaneously analyzed along the western and northern coast of the Iberian Peninsula in terms of wind forcing and water temperature response. The wind forcing analysis showed that the season under more upwelling favorable conditions corresponds to spring–summer (April–September) along the western coast and only to summer (June–August) along the northern one. Taking into account the upwelling period common to both coasts (June–August), it was observed that the occurrence of upwelling events simultaneously along both coasts is the most probable situation (∼46%) followed by upwelling unfavorable conditions also along both coasts (∼26%). The analysis of sea surface temperature data also showed the existence of an upwelling season in spring–summer along both coasts, although upwelling events are more frequent and intense along the western coast than along the northern one. Chlorophyll concentrations showed a high seasonal variability at the western coast with the highest concentrations values in spring–summer months while at the northern coast the maximum values were observed in spring and autumn.